Media Diorama untuk Meningkatkan Hasil Belajar IPA Siswa Kelas V Negeri No.075079 Baruyu Lasara - Yurnis Laowo; Lucky Nindi Riandika Marfu'i (Jurnal Pembelajaran dan Pendidikan Dasar, 2025)
The learning of Natural Sciences can be conducted using methods suitable for the teaching materials. The research aims to determine the application of diorama media in improving the learning outcomes of Science related to the water cycle material in fifth grade students at SD Negeri No. 075079 Baruyu Lasara, South Nias District. The type of research is Classroom Action Research (CAR) comprising 2 cycles. The subjects of the research are fifth-grade students totaling 15, consisting of 8 boys and 7 girls. The study takes place from April to May 2024. The research instruments are observation and written tests. The results of the research using diorama media show that in cycle 1, the classical learning completeness of students was 53%, and in cycle 2, it showed a completeness percentage of 100%. In other words, many students who passed (above the Minimum Passing Criteria) in the research results of cycle 1 were only 8 students who passed. After improvements in learning were made using diorama media in cycle 2, the number of students who passed increased by 15, and they were declared to have met the Minimum Passing Criteria. This proves that the use of diorama media in teaching the water cycle material is capable of significantly improving science learning outcomes.